Two training-load paradoxes: Can we work harder and smarter, can physical preparation and medical be teammates? - Gabbett, T. J.; Whiteley, R. (International Journal of Sports Physiology and Performance, 2017)
The authors have observed that in professional sporting organizations the staff responsible for physical preparation and medical care typically practice in relative isolation and display tension as regards their attitudes toward training-load prescription (much more and much less training, respectively). Recent evidence shows that relatively high chronic training loads, when they are appropriately reached, are associated with reduced injury risk and better performance. Understanding this link between performance and training loads removes this tension but requires a better understanding of the relationship between the acute:chronic workload ratio (ACWR) and its association with performance and injury. However, there remain many questions in the area of ACWR, and we are likely at an early stage of our understanding of these parameters and their interrelationships. This opinion paper explores these themes and makes recommendations for improving performance through better synergies in support-staff approaches. Furthermore, aspects of the ACWR that remain to be clarified—the role of shared decision making, risk:benefit estimation, and clearer accountability—are discussed.